PRINCIPLES OF EFFECTIVE ORGANIZATION OF ARTISTIC-AESTHETIC TASTE OF PRIMARY CLASS STUDENTS THROUGH MUSIC - Davladiyarova Shahzoda Komiljon qizi (Web of Journals Publishing, 2024)
This article describes the forms of effective organization of artistic and aesthetic taste of elementary school students through musical means.
Keywords: Perception, high taste, aesthetic spirit, voice, didactic principle.